Hate Speech On Social Media Over The Macedonia Naming Dispute - Neshkovska, Silvana; Trajkova, Zorica (Blaže Koneski Faculty of Philology, Ss. Cyril and Methodius University, Skopje., 2019)
The paper offers a critical discourse and pragmatic analysis of a corpus of hateful Facebook comments of Macedonian citizens over the Macedonia naming dispute, collected immediately after the name change was officially endorsed in the Parliament. The analysis first attempts to unveil who the hateful political discourse in the given socio-political context is directed at, what roles the commenters assume, what speech acts the hateful posts are predominantly composed of (e.g. assertive, directives, expressives, commissives), as well as what kind of negative lexis and rhetorical tropes are employed by the commenters. The main aim of the research is to unveil the main features of hateful comments through detailed language analysis as they could be easily detected and extracted from social media. The results show that social media have influenced the traditional pattern of communication by introducing a more interactive and participative type of communication. Social media users employ them to direct verbal assaults not only at fellow citizens, but also at political figures, journalists, diplomats and other officials, assuming roles of analysts and judges who mostly use assertive and expressive speech acts, ingrained with a variety of negative lexis and rhetorical figures intended to reinforce their negative stance.
Keywords: hate speech, social media, speech acts